2006
DOI: 10.1007/s11249-006-9082-z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and acid droplet size effects in acid neutralization of marine cylinder lubricants

Abstract: Temperature and acid droplet size effects on the rate of acid neutralization by Marine Cylinder Lubricants were investigated by using a heating-capillary video microscopy. The neutralization experiments were performed inside a $200-lm capillary microreactor and the progress of reaction was recorded in real time. Increasing temperature dramatically impacted on the neutralization rate. While the effect of acid droplet size was negligible initially, it might affect the rate as well when a droplet got smaller than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 10 publications
3
25
0
Order By: Relevance
“…26 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 The adsorption-controlled reaction rate constant expression used in the model simulations, Eq. (13), is based on the video-microscopy single droplet experiments performed by Fu et al, 24 who reported a shrinking rate. The present model considers only consumption of entire droplets.…”
Section: Evaluation Of Model Assumptionsmentioning
confidence: 99%
“…26 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 The adsorption-controlled reaction rate constant expression used in the model simulations, Eq. (13), is based on the video-microscopy single droplet experiments performed by Fu et al, 24 who reported a shrinking rate. The present model considers only consumption of entire droplets.…”
Section: Evaluation Of Model Assumptionsmentioning
confidence: 99%
“…Experimental materials and methods were described in detail in our previous report [26]. One difference of the present work is that multiple acid droplets were injected inside the MCL-filled capillary microreactor and monitored through our video-microscopy system [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…One difference of the present work is that multiple acid droplets were injected inside the MCL-filled capillary microreactor and monitored through our video-microscopy system [26,27]. The success of the experiments requires keeping all the injected acid droplets in view so that the progress of neutralization can be recorded and precisely measured [26] at all stages of the experiments. The disappearing rate of each acid droplet is characterized by radius change with time [26], which includes both the rates of acid neutralization and solubilization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of reaction increases with temperature possibly because the number of water droplets increases with temperature by breakup of large droplets, so enhancing the probability of encounter with an OD particle. 15,19,20 The surfactant molecules on the surface of the nanoparticle and the acid droplet can at least partially exchange on 'collision', exposing the CaCO 3 more effectively to the acid and subsequent neutralization.…”
Section: Introductionmentioning
confidence: 99%